Exploiting Glutamine Consumption in Atherosclerotic Lesions by Positron Emission Tomography Tracer (2S,4R)-4-18F-Fluoroglutamine - Palani, Senthil; Miner, Maxwell W. G.; Virta, Jenni; Liljenbäck, Heidi; Eskola, Olli; Örd, Tiit; Ravindran, Aarthi; Kaikkonen, Minna U.; Knuuti, Juhani; Li, Xiang-Guo; Saraste, Antti; Roivainen, Anne (Frontiers in Immunology, 2022)
Increased glutamine metabolism by macrophages is associated with development of atherosclerotic lesions. Positron emission tomography/computed tomography (PET/CT) with a glutamine analog (2S,4R)-4-18F-fluoroglutamine (18F-FGln) allows quantification of glutamine consumption in vivo. Here, we investigated uptake of 18F-FGln by atherosclerotic lesions in mice and compared the results with those obtained using the glucose analog 2-deoxy-2-18F-fluoro-D-glucose (18F-FDG). Uptake of 18F-FGln and 18F-FDG by healthy control mice (C57BL/6JRj) and atherosclerotic low density lipoprotein receptor-deficient mice expressing only apolipoprotein B100 (LDLR−/−ApoB100/100) was investigated. The mice were injected intravenously with 18F-FGln or 18F-FDG for in vivo PET/CT imaging. After sacrifice at 70 minutes post-injection, tracer uptake was analyzed by gamma counting of excised tissues and by autoradiography of aorta cryosections -, together with histological and immunohistochemical analyses. We found that myocardial uptake of 18F-FGln was low. PET/CT detected lesions in the aortic arch, with a target-to-background ratio (SUVmax, aortic arch/SUVmean, blood) of 1.95 ± 0.42 (mean ± standard deviation). Gamma counting revealed that aortic uptake of 18F-FGln by LDLR−/−ApoB100/100 mice (standardized uptake value [SUV], 0.35 ± 0.06) was significantly higher than that by healthy controls (0.20 ± 0.08, P = 0.03). More detailed analysis by autoradiography revealed that the plaque-to-healthy vessel wall ratio of 18F-FGln (2.90 ± 0.42) was significantly higher than that of 18F-FDG (1.93 ± 0.22, P = 0.004). Immunohistochemical staining confirmed that 18F-FGln uptake in plaques co-localized with glutamine transporter SLC7A7-positive macrophages. Collectively these data show that the 18F-FGln PET tracer detects inflamed atherosclerotic lesions. Thus, exploiting glutamine consumption using 18F-FGln PET may have translational relevance for studying atherosclerotic inflammation.